Trend of critical thinking skill studies in mathematics education: A study design to data analysis - Pujia Siti Balkist; Dadang Juandi (SAINTIS Publishing, 2022)
The aim of this study was focuses on the analysis of international publications related to critical thinking skills in education including the number of publications and how they trend, the distribution of study countries, study types, study subjects, critical thinking linkages that arise from published publications. analyzed, data collection instruments, data analysis and results of study on these publications. the most distribution of data related to critical thinking skills in 2021 with the distribution of countries namely Indonesia, USA, Iran, Malaysia, Turkey, UAE and the most publications obtained by Indonesia. The most common type of study is qualitative study, followed by quantitative study and then study and development. The study subjects used in the article are quite spread out from early childhood, elementary school students, junior high school students, high school students, university students, teachers to the books used. Most of the study trends discussed here relate to teacher pedagogical competence, problem solving, achievement, creative thinking, peer shared intervention and communication skills as a form of cooperation in 21st century skills. Test instruments are used the most, then questionnaires, interviews, continued questionnaire and observation guide, systematic literature review and finally book scoring. data analysis using percentage is the most, data analysis with descriptions then t test and ANOVA.